(untitled) (Brazilian Journal of Oceanography, 2019)
This study describes the taxonomic composition and horizontal distribution of Serranidae larvae along the Southeastern Brazilian Bight (SBB, approximately 22°S and 28°S), and investigates how environmental and biological factors influence the larval distribution. Ichthyoplankton samples were collected in 10 oceanographic cruises conducted from 1975 to 1981. Serranidae larvae were identified into 15 species, including 11 genera and four subfamilies. Except for Diplectrum formosum, which was widely distributed throughout the SBB, Hyporthodus spp. and Baldwinella vivanus were distributed in the southern portion of the SBB, while other species were distributed mainly in the northern portion of the SBB, inside the 200 m isobath. Local depth, latitude, distance from the closest island and salinity were factors that influenced significantly on the distribution and abundance of the most abundant taxa D. formosum, Diplectrum spp., Serranus spp. and Mycteroperca spp. Significant progress was made in identifying grouper larvae from the SBB (Epinephelus morio, Epinephelus itajara and Hyporthodus nigritus).